New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae: Heteropodinae) - Guala, Mariel E.; Labarque, Facundo M.; Rheims, Cristina A. (Zootaxa, 2012)
Two new species of Anaptomecus Simon, 1903 are described based on males and females from Ecuador: A. paru sp. nov.,from Santo Domingo, Santo Domingo de Tsáchilas, and A. suni sp. nov., from Puerto Napo, Napo. Both species sharewith other Anaptomecus species the following characters: an elongated opisthosoma; male palp with U-shaped sperm ductloop in ventral view, hyaline conductor situated on a membranous base; female epigynum with posterior lobes and spermathecae with glandular projections.